Pitfalls and Possibilities in the Analysis of Biomass Allocation Patterns in Plants - Poorter, Hendrik; Sack, Lawren (Frontiers in Plant Science, 2012)
Plants can differentially allocate biomass to leaves, stems, roots and reproduction, and follow ontogenetic trajectories that interact with the prevailing climate. Various methodological tools exist to analyse the resulting allocation patterns, based either on the calculation of biomass ratios or fractions of different organs at a given point in time, or on a so-called allometric analysis of biomass data sampled across species or over an experimental growth period. We discuss the weak and strong points of each of these methods. Although both approaches have useful features, we suggest that often a plot of biomass fractions against total plant size, either across species or in the comparison of treatment effects, combines the best of both worlds.